2010
DOI: 10.1097/hjh.0b013e328333226c
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Digibind with endogenous cardiotonic steroids from preeclamptic placentae

Abstract: Background-Preeclampsia (PE) is a major cause of maternal and fetal mortality, and its pathogenesis is not fully understood. Endogenous digitalis-like cardiotonic steroids (CTS) have been implicated in the pathophysiology of PE; this is illustrated by clinical observations that Digibind, a therapeutic digoxin antibody fragment which binds CTS, lowers blood pressure and reverses Na/KATPase inhibition in patients with PE. Recently we reported that plasma levels of marinobufagenin (MBG), a bufadienolide vasoconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 26 publications
7
32
0
Order By: Relevance
“…Previously, we demonstrated that in patients with preeclampsia-elevated plasma, MBG levels were associated with the inhibition of erythrocyte Na/K-ATPase which was reversible by both 3E9 mAb and Digibind [14] and that in preeclamptic placentae, bufadienolide CTS, including MBG, rather than EO, represents a target for Digibind [27]. In the present study, both 3E9 mAb and Digibind ex vivo restored activity of Na/K-ATPase in erythrocytes from patients with CKD.…”
Section: Discussionsupporting
confidence: 67%
“…Previously, we demonstrated that in patients with preeclampsia-elevated plasma, MBG levels were associated with the inhibition of erythrocyte Na/K-ATPase which was reversible by both 3E9 mAb and Digibind [14] and that in preeclamptic placentae, bufadienolide CTS, including MBG, rather than EO, represents a target for Digibind [27]. In the present study, both 3E9 mAb and Digibind ex vivo restored activity of Na/K-ATPase in erythrocytes from patients with CKD.…”
Section: Discussionsupporting
confidence: 67%
“…MBG has been identified in the placenta, and its increase in preeclampsia have been well documented (22). In our study in offspring of dams on HS or LS, the expression of ␣ 1 -Na ϩ -K ϩ -ATPase in fetal kidneys at term was decreased in parallel with the elevation of MBG resembling the decrease of plasmalemmal ␣ 1 -Na ϩ -K ϩ -ATPase observed in response to MBG in vitro (41).…”
Section: F351supporting
confidence: 65%
“…Previous research by ourselves 27 and others [28][29][30][31][32] had indicated that an SP inhibitor or EDLF exists in placental homogenates, with higher amounts observed in placenta from women having PE. Our initial hypothesis in this study was that the placenta produces such an EDLF.…”
Section: Resultsmentioning
confidence: 99%